Three‐dimensional cardiac print assisted percutaneous closure of left ventricular pseudoaneurysm in patient with Behçet's disease. Issue 2 (26th February 2021) - Quimby, Donald L.; Ford, Jonathan; Tanner, Gregory J.; Mencer, Nicholas; Decker, Summer; Matar, Fadi
Abstract: Spontaneous left ventricular pseudoaneurysms are very rare and can have catastrophic consequences if unrecognized. A case of combined spontaneous left ventricular aneurysm and pseudoaneurysm in Behcet's disease (BD) has been reported. The case emphasizes advanced techniques for percutaneous closure of the defects with the use of an ex‐vivo three‐dimensional cardiac printed model as a tool to facilitate the procedure.